Fiber Surface Modification; Characterization of Rattan Fiber Reinforced Composite - Elvistia Firdaus, Flora; Dachyar, M (International Journal of Engineering and Technology, 2018)
Increasing the awareness of global warming and the depletion of petroleum resources had made many researchers focuses on using natural materials such as rattan. Its an edible fibers  are prepared to reinforce matrix yielding composite products within the aid of epoxy based resin  and hardener which also perform  as catalyst. The fibres are previously conducted an alkali treatment, this was considered to enhance the cohessiveness of fibers to matrix. Silane and dimethylethanolamine (DMEA) as an adhesives booster is respectively added to the composite formula. The specific purpose of this research is to know the influence of addition of Silane and  DMEA to the final properties of composite; flexural, tensile strength, elongation at break, hardness, and thermal. From the test results it is found that Silane keeps the matrix amorphous, while the addition of DMEA formed crystalline polymer. The ultimate property of the composites are found also depends on fiber woven pattern.